2013
DOI: 10.6026/97320630009673
|View full text |Cite
|
Sign up to set email alerts
|

Molecular distribution of amino acid substitutions on neuraminidase from the 2009 (H1N1) human influenza pandemic virus

Abstract: The pandemic influenza AH1N1 (2009) caused an outbreak of human infection that spread to the world. Neuraminidase (NA) is an antigenic surface glycoprotein, which is essential to the influenza infection process, and is the target of anti-flu drugs oseltamivir and zanamivir. Currently, NA inhibitors are the pillar pharmacological strategy against seasonal and global influenza. Although mutations observed after NA-inhibitor treatment are characterized by changes in conserved amino acids of the enzyme catalytic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…All pH1N1pdm09 strains sampled in Uganda, Senegal, Mauritania, Kenya, and South Africa had V106I and N248D in the catalytic site (CS) of their N1 proteins relative to the A/California/07/2009(H1N1) strain [ 47 , 48 , 54 , 55 , 56 , 104 ]. Quiliano et al observed 26 unique substitutions among N1 proteins of 59 Africa H1N1pdm09 strains sampled between 2009 and April 2011, with the highest frequency of substitutions in the transmembrane (TM) and L21 domains [ 64 ]. Kenya pH1N1pdm09 strain nucleoproteins (NP) and matrix protein (M1 and M2) sequences sampled in 2009 were 98.8–99.6% and 98–100%, similar to the A/California/07/2009(H1N1) strain, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All pH1N1pdm09 strains sampled in Uganda, Senegal, Mauritania, Kenya, and South Africa had V106I and N248D in the catalytic site (CS) of their N1 proteins relative to the A/California/07/2009(H1N1) strain [ 47 , 48 , 54 , 55 , 56 , 104 ]. Quiliano et al observed 26 unique substitutions among N1 proteins of 59 Africa H1N1pdm09 strains sampled between 2009 and April 2011, with the highest frequency of substitutions in the transmembrane (TM) and L21 domains [ 64 ]. Kenya pH1N1pdm09 strain nucleoproteins (NP) and matrix protein (M1 and M2) sequences sampled in 2009 were 98.8–99.6% and 98–100%, similar to the A/California/07/2009(H1N1) strain, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 90% of global H1N1 strains sampled between 2008 and 2009 were oseltamivir-resistant but sensitive to zanamivir [ 122 ]. Oseltamivir-resistant H1N1pdm09 strains were sporadically circulated in South Africa [ 43 ], globally between 2009 and 2011 [ 64 , 95 , 122 ], the Middle East and North Africa in 2015 [ 91 ], and Myanmar in 2017 [ 129 ]. However, there is no sufficient evidence that the resistant H1N1pdm09 variants resulted from oseltamivir treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the poor coverage of vaccination makes the prophylaxis of influenza ineffective. The mutation of neuraminidase (NA) also created a lot of oseltamivir-resistant influenza strains;39 hence, reinforcing development of new prophylactic and therapeutic tools is necessary according to the surveillance results of annual influenza epidemic.…”
Section: Discussionmentioning
confidence: 99%